International Migration: Major Challenges and Analysis of Human Resource Management for Supply Chains - Phong Thanh Nguyen; Quyen Le Hoang Thuy To Nguyen; Rahul Chauhan; Wahidah Hashim; Andino Maseleno; Vy Dang Bich Huynh; Ngoc Bich Vu; Loan Phuc Le; Khoa Dang Vo; Phuong Thanh Phan (International Journal of Supply Chain Management, 2019)
This article discusses the arguments in favor of and against a right to mobility by considering human resource managements for the supply chains. It argues that contemporary migration and border policies are largely restrictive but still fail to meet their announced objectives which call for alternative approaches to international human resource management. From a human rights viewpoint, tight border controls are accompanied by major challenges; including trafficking, the refuge crisis, and the death and vulnerability of irregular migrants; which ultimately threaten the moral foundations of liberal democracies. In this context, a right to mobility may constitute a relevant answer and the article examines the implications of such a right in terms of supply chain management, social cohesion, economic wealth, security, and border/migration governance.